CARBON GEOCHEMISTRY OF NATURAL APATITES: EVIDENCE FROM PHYSICOCHEMICAL STUDIES - Gilinskaya L.G.; Grigor'eva T.N.; Korneva T.A.; Stolpovskaya V.N.; Zanin Yu.N. (My University, 2001)
Spectroscopic methods and thermal analysis were used to study carbon in genetically different apatites. Carbon incorporation in the structure, as CO32- reversible arrow PO43- and, at the surface, as CO2, thermal behavior, and bond strength are controlled by structural water, which is present as H2O and whose content depends on the conditions of apatite formation (mainly on pH). Apatite with structural H2O and CO2 is characterized by poorer crystallinity and is covered by an amorphous CO2. nH(2)O layer responsible for mineral solubility. The obtained data are based on observations of CO2-, CO3-, CO33-, and their isotropic and anisotropic paramagnetic radicals.